STABILITY OF UNDERWATER STRUCTURE UNDER WAVE ATTACK - C. Paotonan; D. B.P. Allo (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2011)
Geotube is, among others, a type of coastal structure that is increasingly accepted for coastal protection especially underwater breakwater. Besides its relatively low cost, it has other advantages such as flexibility, ease of construction and the fact that it can be filled with local sand material. Similar to all other coastal structures, it should also be stable under wave attack. A simple theoretical approach based on linear wave was adopted to estimate the stability of such structure. The theoretical solution was then compared with an experimental study. The experimental study was conducted at the Hydraulics and Hydrology Laboratory of Universitas Gadjah Mada. However, instead of a real geotube, PVC pipe was used where the weight of the PVC was varied by adjusting the volume of sand in the pipe. The result indicated that the agreement between the theoretical solution and the experiment was encouraging. The analytical solution may be utilized to predict underwater pipe stability under wave attack with certain degree of accuracy.